Four-dimensional imaging and quantification of viscous flow sintering within a 3D printed bioactive glass scaffold using synchrotron X-ray tomography - A. Nommeots-Nomm; C. Ligorio; A.J. Bodey; B. Cai; J.R. Jones; P.D. Lee; G. Poologasundarampillai (Materials Today Advances, 2019)
Bioglass® was the first material to form a stable chemical bond with human tissue. Since its discovery, a key goal was to produce three-dimensional (3D) porous scaffolds which can host and guide tissue repair, in particular, regeneration of long bone defects resulting from trauma or disease. Producing 3D scaffolds from bioactive glasses is challenging because of crystallization events that occur while the glass particles densify at high temperatures. Bioactive glasses such as the 13–93 composition can be sintered by viscous flow sintering at temperatures above the glass transition onset (Tg) and below the crystallization temperature (Tc). There is, however, very little literature on viscous flow sintering of bioactive glasses, and none of which focuses on the viscous flow sintering of glass scaffolds in four dimensions (4D) (3D + time). Here, high-resolution synchrotron-sourced X-ray computed tomography (sCT) was used to capture and quantify viscous flow sintering of an additively manufactured bioactive glass scaffold in 4D. In situ sCT allowed the simultaneous quantification of individual particle (local) structural changes and the scaffold's (global) dimensional changes during the sintering cycle. Densification, calculated as change in surface area, occurred in three distinct stages, confirming classical sintering theory. Importantly, our observations show for the first time that the local and global contributions to densification are significantly different at each of these stages: local sintering dominates stages 1 and 2, while global sintering is more prevalent in stage 3. During stage 1, small particles coalesced to larger particles because of their higher driving force for viscous flow at lower temperatures, while large angular particles became less faceted (angular regions had a local small radius of curvature). A transition in the rate of sintering was then observed in which significant viscous flow occurred, resulting in large reduction of surface area, total strut volume, and interparticle porosity because the majority of the printed particles coalesced to become continuous struts (stage 2). Transition from stage 2 to stage 3 was distinctly obvious when interparticle pores became isolated and closed, while the sintering rate significantly reduced. During stage 3, at the local scale, isolated pores either became more spherical or reduced in size and disappeared depending on their initial morphology. During stage 3, sintering of the scaffolds continued at the strut level, with interstrut porosity reducing, while globally the strut diameter increased in size, suggesting overall shrinkage of the scaffold with the flow of material via the strut contacts.This study provides novel insights into viscous flow in a complex non-idealized construct, where, locally, particles are not spherical and are of a range of sizes, leading to a random distribution of interparticle porosity, while globally, predesigned porosity between the struts exists to allow the construct to support tissue growth. This is the first time that the three stages of densification have been captured at the local and global scales simultaneously. The insights provided here should accelerate the development of 3D bioactive glass scaffolds. Keywords: Glass, Sintering, In situ x-ray tomography, Bioactive, Scaffold, Viscous flow